What deters and why exploring requirements and effective deterrence of interstate aggression - Mazarr, Michael J. 1965- (RAND Corporation, 2018)
The challenge of deterring territorial aggression, which for several decades has been an afterthought in U.S. strategy toward most regions of the world, is taking on renewed importance. An increasingly belligerent Russia is threatening Eastern Europe and the Baltic States with possible aggression, conventional and otherwise. China is pursuing its territorial ambitions in the East and South China Seas with greater force, including the construction of artificial islands and occasional bouts of outright physical intimidation. North Korea remains a persistent threat to the Republic of Korea (ROK), including the possibility of large-scale aggression using its rapidly advancing nuclear arsenal. Yet the discussion of deterrence-as a theory and practical policy requirement-has lagged in U.S. military and strategy circles. The authors aim to provide a fresh look at the subject in this context, with two primary purposes: to review established concepts about deterrence, and to provide a framework for evaluating the strength of deterrent relationships. For greater focus, they concentrate on a specific category or form of deterrence: extended deterrence of interstate aggression. The authors consider the requirements for the United States to deter potential aggressors abroad from attacking U.S. allies or other countries in large-scale conventional conflicts. Examples include Russian attacks on the Baltic States and a North Korean assault on the ROK. The study stems from a specific research question: What are the requirements of effective extended deterrence of large-scale military aggression? The focus is therefore on the criteria that tend to distinguish successful from unsuccessful efforts to deter interstate aggression
Keywords: Abschreckung; Strategie; Außenpolitik; USA; Deterrence (Strategy)